Swing profiles in sport: An accelerometer analysis - Thiel, D. V.; Sarkar, A. K. (Procedia Engineering, 2014)
Inertial accelerometer sensors record movement. Rhythmic and repetitive movement is common to almost all sporting activities. It is possible to model the dynamic acceleration of a swing (both body and implement) using a cosine squared function of angular position with time. In cricket, a straight drive using a bat mounted accelerometer can be well matched (r > 0.9) and the time and effort determined. The same analysis can be applied to baseball, field hockey, boxing and running.